(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To assess urinary albumin excretion in pre-eclamptic women by shorter timed collection of urine from 12 hours night sample. Method: This cross sectional study was carried out in the Department of Obstetric and Gynaecology, Bangabandhu Sheikh Mujib Medical University, and Dhaka Medical College Hospital, during the period of November 2004 to February 2005. Among the admitted patient total 40 pregnant women with pre-eclampsia were taken with proper selection criteria. The criteria for selection were hypertension (140/90 mmHg or more) after 20th week of gestation and a bed side urine albumin test positive. Detailed medical and obstetric history was taken and thorough examination was done and all the informations were recorded in the pre-designed data collection sheet. Results: The mean± SD urinary albumin in 12 hour day, 12 hour night and 24 hour sample were 1.74+0.51 gm/L, 1.76+0.51 gm/L and1.75+0.54 gm/L respectively. Urinary albumin concentration in the 12 hour day & night samples agreed well with concentration of the 24 hour samples. Conclusion: From the result it could be concluded that albumin concentrations in the 12- hours day and 12-hours night collections were close to the concentrations of the 24-hour collection. Bangladesh J Obstet Gynaecol, 2012; Vol. 27(1) : 9-13